ANALYSIS OF ENERGY SAVING AND ENERGY EFFICIENCY ISSUES DURING OPERATION OF THE METRO ROLLING STOCK - Donchenko, A. V.; Sulym, A. O.; Siora, A. S.; Melnyk, A. A.; Fedorov, V. V. (Science and Transport Progress, 2016)
Purpose.Nowadays a problem of significant power consumption of the rolling stock during its operation is a current issue. In connection with staged electricity rates increase further development of the rail electric transport, including metro rolling stock is impossible without a use of modern energy saving solutions and energy-efficient systems. To solve the specified problem it is necessary to carry out analysis of measures and determine prospective directions in energy saving and increase of energy efficiency on the metro rolling stock. Methodology. Using methods of scientific analysis, generalization, comparative analysis, forecasting and using results of experimental studies, the authors determined main ways for reduction of energy consumption during operation of the metro rolling stock. Energy cost analysis for metro rolling stock of the public utility (PU) «Kiev Metro» was carried out. A great number of research works of native and foreign authors concerning the above mentioned problem were analyzed. Findings. Principal directions in energy saving and increase of energy efficiency of the metro rolling stock are implementation of recuperation systems, energy storage systems and energy-efficient control systems. It was determined that implementation of recuperation and energy storage systems helps to save a considerable amount of energy, consumed for traction, but it involves substantial investments. It is pointed out that in current complicated conditions of economic development of Ukraine, use of energy-efficient control systems is a perspective direction in energy saving. Main advantage of this direction is the economic effect obtaining without significant investments. Originality. For the first time was performed potential assessment for energy saving as a result of energy-efficient control systems use at type routine rolling stock operation modes on sections «Khreschatik –Teatralnaya – Khreschatik» and «Shulyavskaya –Beresteyskaya –Shulyavskyaya» of KP «Kiev Metro». Practical value. Results of the research concerning quantity of energy saved with the help of recuperation systems and energy saving control systems can be used during building of a new metro rolling stock or modernization of existing one.